2020
DOI: 10.3389/frai.2020.578613
|View full text |Cite
|
Sign up to set email alerts
|

Prognostics and Health Management of Industrial Assets: Current Progress and Road Ahead

Abstract: Prognostic and Health Management (PHM) systems are some of the main protagonists of the Industry 4.0 revolution. Efficiently detecting whether an industrial component has deviated from its normal operating condition or predicting when a fault will occur are the main challenges these systems aim at addressing. Efficient PHM methods promise to decrease the probability of extreme failure events, thus improving the safety level of industrial machines. Furthermore, they could potentially drastically reduce the ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 205 publications
0
31
0
Order By: Relevance
“…There are a large number of excellent articles within the PHM literature that have led to health management advances that are being deployed today for real-world use-cases [27,28] . However, many of these are applicationspecific methods, when viewed from a larger context of SLP are difficult to generalize across systems or applications [29,30] .…”
Section: Model Basedmentioning
confidence: 99%
“…There are a large number of excellent articles within the PHM literature that have led to health management advances that are being deployed today for real-world use-cases [27,28] . However, many of these are applicationspecific methods, when viewed from a larger context of SLP are difficult to generalize across systems or applications [29,30] .…”
Section: Model Basedmentioning
confidence: 99%
“…Over the last few years, different types of DNNs have been developed for RUL prediction, ranging from relatively complex fully-connected networks to Convolutional Neural Networks [29]- [31] and Recurrent Neural Networks [32]- [34]. DL models have shown promising performance in estimating the RUL from sensor data on prognostics benchmark datasets [35], [36] using several different network architectures (see [8] for an extensive review). More sophisticated extensions to the aforementioned standard architectures have also recently been applied to prognosis, including attention mechanisms [37] and capsule neural networks [38].…”
Section: A Deep Learning Techiques In Progosticsmentioning
confidence: 99%
“…While Deep Neural Networks (DNN) have delivered their most prominent achievements in the fields of Computer Vision and Natural Language Processing, recent research works have shown their effective use also for prognostics [7], VOLUME 4, 2016 [8]. DNNs owe a great part of their success to their large representation power and to their capacity of learning sets of hierarchical features across their multilayer architectures directly from raw data.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, different types of DNNs have been developed for RUL prediction, ranging from relatively complex fully-connected networks to Convolutional Neural Networks (CNN) [23][24][25] and Recurrent Neural Networks (RNN) [26][27][28]. DL models have shown promising performance in estimating the RUL from sensor data on prognostics benchmark datasets [29,30] using several different network architectures (see [47] for an extensive review). More sophisticated extensions to the aforementioned standard architectures have also recently been applied to prognosis, including attention mechanisms [68] and capsule neural networks [71].…”
Section: Related Work 21 DL Techiques In Progosticsmentioning
confidence: 99%
“…While Deep Neural Networks (DNN) have delivered their most prominent achievements in the fields of Computer Vision (CV) and Natural Language Processing (NLP), recent research works have shown their effective use also for prognostics [47,70]. DNNs owe a great part of their success to their large representation power and to their capacity of learning sets of hierarchical features across their multilayer architectures directly from raw data.…”
Section: Introductionmentioning
confidence: 99%